Trends of ESD Oriented RADEC Learning Model in Elementary Education: Review and Bibliometric Analysis - Hana Lestari; Ima Rahmawati; Mohammad Ali; Wahyu Sopandi; Ana Ratna Wulan (Postgraduate, University of Mataram, 2023)
The purpose of the study was to provide a thorough bibliometric assessment of the literature on the RADEC (Read, Answer, Discuss, Explain, and Create) learning model for primary schools that are oriented toward education for sustainable development. articles discovered using the Google Scholar database and the Publish or Perish software (PoP). From 2015 to 2022, 200 papers were located in the Google Scholar database. Utilizing the reference manager Zotero, the chosen articles were then managed. The researcher organized the database, and then used VOS-viewer software to categorize and visualize it. The results are based on research, it is necessary to implement ESD that develops sustainability consciousness competencies, namely abilities that include knowledge about sustainable development, attitudes, and behaviors that contribute to achieving the Sustainable Development Goals (SDGs). It is necessary to apply a model that has adequate steps to develop the competence of sustainable consciousness. One of the solutions carried out by researchers is implementing ESD through the ESD-oriented RADEC learning model. Through the development of the ESD-oriented RADEC learning model, it is hoped that it will be able to provide knowledge and skills in environmentally friendly practices and even stick to sustainable attitudes and behavior in each student. The implementation of the ESD-oriented RADEC model can be applied to all disciplines, not only environmental education.